Antibacterial Activity Test of Nipa Palm Leaf Extract (Nypa fruticans) Against Staphylococcus epidermidis - Rury Trisa Utami; Sri tati Rukiyani (Jurnal EduHealth, 2026)
Skin disorders are a common health problem and can be caused by pathogenic bacterial infections. Staphylococcus epidermidis bacteria are known to play a role in various infections that can affect the skin surface. The use of natural ingredients as alternative antibacterial agents is crucial, one of which is nipah leaves (Nypa fruticans), which contain various secondary metabolites with potential antibacterial activity. This study aimed to determine the antibacterial activity of nipah leaf ethanol extract against two test bacteria and to determine the most effective concentration. Antibacterial testing used the disc diffusion method at concentrations of 200 μg/disc, 300 μg/disc, and 400 μg/disc, with chloramphenicol as a positive control and DMSO as a negative control. The results showed that nipah leaf extract formed a zone of inhibition at all tested concentrations. The largest zone of inhibition was found at a concentration of 400 μg/disc, measuring 8,2 mm against Staphylococcus epidermidis, which is classified as having medium inhibitory activity.